2016
DOI: 10.1142/s1793984416500070
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Heating of Fe–Co Ferrites — Experiments and Modeling

Abstract: Magnetic nanoparticle hyperthermia uses magnetically-induced heat to kill cancer cells. In an alternating magnetic field, the induced heat depends strongly on particles’ absorption properties. In order to achieve and maintain therapeutic temperatures inside a tumor and to minimize damage to normal tissues due to induced eddy currents, there is a need to develop new magnetic nanoparticles with improved heating characteristics. This paper investigates the magnetic heating properties of composite iron-cobalt ferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Several studies have reported that the heating response of CoFe alloy nanoparticles to a variable magnetic field could be determined by regulating the proportion of cobalt. 48 , 49 Compared to magnetite (Fe 3 O 4 ) and cobalt ferrite (CoFe 2 O 4 ) MNPs, CoFe NPs with an adjustable thermal response exhibit high-efficiency therapeutic potential and specific loss power (SLP) in tumors. 49 , 50 …”
Section: Classification Of Mnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that the heating response of CoFe alloy nanoparticles to a variable magnetic field could be determined by regulating the proportion of cobalt. 48 , 49 Compared to magnetite (Fe 3 O 4 ) and cobalt ferrite (CoFe 2 O 4 ) MNPs, CoFe NPs with an adjustable thermal response exhibit high-efficiency therapeutic potential and specific loss power (SLP) in tumors. 49 , 50 …”
Section: Classification Of Mnpsmentioning
confidence: 99%
“… 48 , 49 Compared to magnetite (Fe 3 O 4 ) and cobalt ferrite (CoFe 2 O 4 ) MNPs, CoFe NPs with an adjustable thermal response exhibit high-efficiency therapeutic potential and specific loss power (SLP) in tumors. 49 , 50 …”
Section: Classification Of Mnpsmentioning
confidence: 99%